Bone involvement in patients with cervical carcinoma: a single-institution cohort study. Issue 2 (3rd July 2019) - Butt, JL; Botha, MH
Abstract : Introduction: Bony metastases in cervical carcinoma are rare; however, autopsy studies indicate that they are underdiagnosed. A retrospective study was undertaken to describe the risk factors and tumour characteristics and estimate the prevalence of bone involvement in women with cervical cancer at a tertiary institution in South Africa. Methods: A retrospective cohort analysis of women with cervical cancer diagnosed between 2014 and 2015 was undertaken. Demographic, treatment and follow-up data were collected for all women with bone metastases confirmed by imaging. Descriptive statistics were generated. Results: The study identified 642 patients with cervical carcinoma, of whom 25 (3.89%) were diagnosed with bone involvement. Ten women had bone involvement at diagnosis and 15 women at recurrence, occurring a median of 286 days after primary treatment. Survival after the diagnosis of bone metastases was short, with 88% of patients dying within six months. The WHO performance status score at diagnosis was a significant predictor of survival ( p = 0.024). A prognostic score was utilised and those with a high score had a significantly shorter survival (median 61 days) than those with a low score (median 158 days) ( p = 0.0065). Conclusions: Although bone metastases are rare in women with cervical cancer, they are important to recognise. Healthcare workers should be vigilant regarding increased analgesic use and chronic pain, as these may indicate bone involvement. As survival is short, a prognostic score is valuable in tailoring treatment. A patient's quality of life may be greatly improved by an appropriate radiotherapy and palliative care plan.